Epistemology towards The management Of the XXI century (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2018)
The purpose of this essay is to reflect on the epistemological approaches of management, oriented towards their contributions in the formation of the new manager of the 21st century. For which a documentary review was carried out, where constructs such as management, management training, positivist and constructivist epistemology are examined. In addition to recent trends in managerial epistemology, such as complexity and holistic. It is analyzed through epistemology which or which are the most suitable perspectives to direct the training for the current management praxis. From this epistemological reflection, we look for the possibilities of integrating and complementing the different approaches in what I call an epistemological encounter for managerial training.
Keywords: management; management training; epistemology